The effect of CT-based cardiothoracic ratio on survival of COVID-19 patients - Akman, Burcu; Kaya, Ahmet Turan; Çetin, Şirin (The European Research Journal, 2023)
Objectives: We aimed to investigate the relationship between computed tomography (CT)- based cardiothoracic ratio (CTR) with mortality rates of COVID-19 patients. Methods: Our study was a single-center retrospective analysis of 484 patients (aged ≥ 18) who were admitted to our hospital’s emergency department. We included only laboratory-confirmed COVID-19 patients who underwent chest CT. Data of demographic information, laboratory findings, survivals, and chest CT imaging findings were recorded. The radiologist calculated CTR by dividing the greatest transverse cardiac diameter by the greatest transverse thoracic diameter on the initial chest CT. Cardiomegaly was defined if “CTR > 0.5”. Results: Thirty (6.2%) patients were treated as outpatients, and 135/484 (%27.9) patients were treated in the intensive care unit (ICU). A total of 147 /484 (30.4%) patients died. We found a statistical association between cardiomegaly with mortality rates (p < 0.001) and ICU admission (p = 0.008). In multivariate analysis, older age was 1.07-fold (p